THE EFFECT OF GADGET USE INTENSITY DURING THE COVID-19 PANDEMIC ON EMOTIONAL INTELLIGENCE OF EARLY CHILDHOOD - Ayu Nurjanah; Daviq Chairilsyah; Yeni Solfiah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
The rapid development of today's era makes children no stranger to gadgets, the sophistication of gadgets causes children to always want to use them, so it can cause an addiction effect. The covid-19 pandemic has resulted in children tending to spend time with gadgets. This study aims to determine the effect of the intensity of using gadgets during the covid-19 pandemic on the emotional intelligence of early childhood. This research is a quantitative correlation research with statistical test using Chi Square test. The results of this study indicate that the intensity of gadget use in TK Tembilahan District is in the high category, with a high percentage of 41%, medium 36% and low 23%, and children's emotional intelligence is in the medium category with an empirical score of 19.10 this shows that there is a significant correlation. Significant intensity of gadget use during the covid-19 pandemic on the emotional intelligence of children aged 5-6 years in Tembilahan District Kindergarten